Prevalence of Farmer's Lung in Scotland: A Pilot Survey. Issue 5799 (26th February 1972) - Grant, I. W. B.; Blyth, W.; Wardrop, Violet E.; Gordon, R. M.; Pearson, J. C. G.; Mair, A.
Abstract : In a survey of the farming population of Orkney, Ayrshire, and East Lothian the prevalence of farmer's lung was estimated at 86 per 1, 000 in both Orkney and Ayrshire and 23 per 1, 000 in East Lothian. If cases with a negative farmer's lung hay (F.L.H.) precipitin test are excluded these figures are reduced to 43, 36, and nil respectively, but those for Orkney and Ayrshire are still about 20 times higher than any figure previously reported for the prevalence of farmer's lung in Britain. Regional variations in prevalence are probably related both to climatic conditions and to differences in agricultural methods, the latter often being dictated by economic circumstances. Nevertheless the prevalence of farmer's lung could be reduced considerably by the energetic application of preventive measures, backed by financial incentives. The most important of these are efficient drying of hay and cereals before storage, more extensive use of silage, better ventilation of farm buildings, and the introduction of mechanical feeding systems. Individual farmworkers could be taught how to recognize the early symptoms of the disease and encouraged to wear respirators when handling mouldy fodder.